2011
DOI: 10.1038/nature09922
|View full text |Cite
|
Sign up to set email alerts
|

Gut flora metabolism of phosphatidylcholine promotes cardiovascular disease

Abstract: Metabolomics studies hold promise for discovery of pathways linked to disease processes. Cardiovascular disease (CVD) represents the leading cause of death and morbidity worldwide. A metabolomics approach was used to generate unbiased small molecule metabolic profiles in plasma that predict risk for CVD. Three metabolites of the dietary lipid phosphatidylcholine, namely choline, trimethylamine N-oxide (TMAO), and betaine, were identified and then shown to predict risk for CVD in an independent large clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

115
4,616
19
64

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 4,589 publications
(5,009 citation statements)
references
References 63 publications
(65 reference statements)
115
4,616
19
64
Order By: Relevance
“…A previous report showed that TMAO enhanced uptake of cholesterol in peritoneal macrophages, a critical step in atherosclerosis 1. Although we did not observe TMAO inducing inflammation in macrophages, these observations could be due to differential regulation of receptor or signaling mechanisms across cell types.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…A previous report showed that TMAO enhanced uptake of cholesterol in peritoneal macrophages, a critical step in atherosclerosis 1. Although we did not observe TMAO inducing inflammation in macrophages, these observations could be due to differential regulation of receptor or signaling mechanisms across cell types.…”
Section: Discussioncontrasting
confidence: 87%
“…TMAO is derived primarily from dietary choline and carnitine through the action of gut microbiota, which metabolize these constituents to trimethylamine (TMA) 1, 11, 12. TMA is absorbed in turn and travels via the portal circulation to the liver, where it is oxidized by flavin‐containing monoxygenases, primarily FMO3, to TMAO 1, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC is a major dietary source of choline in omnivores, which often is found in the Western diet, such as red meat, eggs, and meat products. Direct ingestion of PC was shown to result in a rise in choline, betaine, and TMAO levels 1, 3. Moreover, previous studies have report that elevated plasma TMAO levels predicted future risk of major adverse cardiovascular events and have a direct mechanistic link to development of cardiovascular disease 1, 2, 3, 4.…”
Section: Discussionmentioning
confidence: 98%
“…Our recent studies in animals and in humans suggested a role for gut microbiota in the pathogenesis of atherosclerosis 1, 2. Trimethylamine‐containing nutrients (eg, PC, choline, and l ‐carnitine) are metabolized by the gut microbiota to trimethylamine (TMA) and converted to TMAO 1.…”
Section: Discussionmentioning
confidence: 99%